Quantificational effect of reforestation to soil erosion in subtropical monsoon regions with acid red soil by sediment fingerprinting - Huang, Changchun; Yang, Hao; Li, Yunmei; Zhang, Mingli; Lv, Heng; Zhu, A-xing; Yu, Yanhong; Luo, Yu; Huang, Tao (Environmental earth sciences, 2017)
Reforestation and afforestation have been implemented over large regions in China for decades, and this has significantly reduced dust storms, desertification and soil/water erosion in China. However, the quantificational evaluation of the reforestation program in China is still incomplete, especially in the southwest China, due to the limitation of survey data. In order to assess the effects of reforestation on soil erosion in southwest China, a subtropical monsoon region with acid red soil, a representative watershed (Dianchi, Yunnan, in southwest China), was selected to study the effect of reforestation on soil erosion over nearly five decades. The land surface soil samples and sedimentary core in this watershed were examined in 2012 to evaluate the soil erosion and sediment deposition during the period of deforestation and reforestation. The results from the multi-source indexes (nutrients, radionuclides, metallic and isotope elements) measurement from soil samples and analyses (composite fingerprinting, remote sensing and geographic information system) indicate that reforestation significantly reduced the presence of sand from surrounding basin via the sedimentary records. Natural forests had the greatest soil conservation capacity, followed by economic forests and farmland, according to a composite fingerprinting. The distribution of total phosphorus, total nitrogen (TN), total organic carbon (TOC) and isotope carbon (δ 13 C SOC ) presents a high consistency to the results of the composite fingerprinting. The loss rate of TN and TOC in farmland is much greater than that in forest. Reforestation will thus increase the storage of TN and TOC in the long term, although this storage is lower than that in farmland during a short time due to the application of fertilizers. The logging of economic forests will significantly increase soil erosion in this region because of low grass coverage. Recommendations include limiting the period of logging in economic forests to periods outside the rainy season and intercropping other kinds of indigenous trees or grasses to reduce soil erosion.